ANALISIS PENETAPAN BIAYA STANDAR TERHADAP PENGENDALIAN BIAYA TENAGA KERJA LANGSUNG PADA PT. ARMADANA GATRA PALEMBANG - Liliana . (Fakultas Ekonomi Universitas Tridinanti Palembang, 2014)
The result of this research shows that based on the analysis of the deviation in direct labor cost in the first period of 2011 and 2012 in PT Armadana Gatra Palembang shows that every year the company has decreased their labor cost,so then it needs to have such an emphasis on working hour so the company could get the result be more efficient an effective. The company also has not used the standard cost well to determine com.The purpose`of this research is to find out how the implementation of standard cost towards the control of direct labor cost in PT Armadana Gatra Palembang. As the variable of the research that used consist of two variable which are the standard cost and direct cost labor. The data that used in this research is secondary data which also use the technique of documentation and literature. Technique data of analysis that used here is the technique of analysis descriptive qualitative because this research is examine about the implamentation of standard cost towards the control of direct labor pany’s effeciency yet, so it caused such a deviations happened to the direct labor cost that already set before. Keyword : Standard cost - the control of labor’s direct cost